(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
The spinel oxides Zn0.4Co0.6AlxFe2-xO4 (x=0.0, 0.25, 0.50, 0.75 & 1.0) have been synthesized in the solid state sintering process in air. X-ray diffraction measurements have been carried out in order to check the phase which showed single phase spinel structure for all the samples. Initial permeability, frequency dependence of the complex permeability sintered at different temperatures has been measured on toroidal samples in the frequency range 1-500 KHz at room temperature. Temperature dependence of the complex permeability has been measured from room temperature to 435Â°C. Transition temperatures (TC) have been estimated from the temperature dependence of the permeability spectra for all the samples. It is found that the values of transition temperatures (TC) and initial permeability (mi) decrease with increasing substitution of Al content in the system. The values of TC obtained from permeability spectra are compared with those obtained from neutron diffraction data and magnetization measurements. doi: 10.3329/jbas.v32i2.2426 Journal of Bangladesh Academy of Sciences Vol.32(2) 2008 201-208